Contribution to the study of earthworms and other groups of mesofauna in the soil of the Bang Ta hilly area, Ba Vi district, Ha Tay province - Kim Hoi, Huynh Thi; Anh, Nguyen Duc (Academia Journal of Biology, 2015)
A total of 12 earthworm species belonging to 5 genera, 4 families, have been firstly recorded in Bangta hilly area, Camlinh village, Bavi district, Hatay province. Among them, the genus Pheretima with the highest number of species (8 species) accounted for 66,8%. 22 other groups of mesofauna have been also recorded here. The number of earthworm species is reverse proportionally to that of other mesofauna groups at the top and the side of the hill. For example, at the hilltop, while no earthworm species was seen, 14 other groups of mesofauna were found. The number of earthworm species and other mesofauna groups decreased from the hillside down the hillbase. In quantitative aspect, on the average, 13.2 ind/m2 and 9.21 g/m2 of earthworms, and 17.6 ind/m2 and 3.38 g/m2 of other groups of mesofauna were respectively evaluated. Pheretima triastriata is the most rich species in density as well as in biomass. This earthworm species may be considered as a potential agent to be used in the amelioration of the soil fertilization.